Neural Mechanism of Altered Limb Perceptions Caused by Temporal Sensorimotor Incongruence - Katayama, Osamu; Tsukamoto, Tatsuya; Osumi, Michihiro; Kodama, Takayuki; Morioka, Shu (Frontiers in Behavioral Neuroscience, 2018)
Previous studies have demonstrated that patients with strokes or chronic pain suffer distorted limb ownership and an inability to perceive their affected limbs as a part of their bodies. These disturbances are apparent in experiments showing time delays between motor commands and visual feedback. The experimental paradigm manipulating temporal delay is considered possible to clarify, in detail, the degree of altered limb perception, peculiarity, and movement disorders that are caused by temporal sensorimotor incongruence. However, the neural mechanisms of these body perceptions, peculiarity, and motor control remain unknown. In this experiment, we used exact low-resolution brain electromagnetic tomography (eLORETA) with independent component analysis (ICA) to clarify the neural mechanisms of altered limb perceptions caused by temporal sensorimotor incongruence. Seventeen healthy participants were recruited, and temporal sensorimotor incongruence was systematically evoked using a visual feedback delay system. Participants periodically extended their right wrists while viewing video images of their hands that were delayed by 0, 150, 250, 350, and 600 ms. To investigate neural mechanisms, altered limb perceptions were then rated using the 7-point Likert scale and brain activities were concomitantly examined with electroencephalographic analyses using eLORETA-ICA. These experiments revealed that peculiarities are caused prior to perceptions of limb loss and heaviness. Moreover, we show that supplementary motor and parietal association areas are involved in changes of peculiarity, limb loss, heaviness, and movement accuracy due to temporal sensorimotor incongruence. We suggest that abnormalities in these areas contribute to neural mechanisms that modify altered limb perceptions and movement accuracy.